HISTOPATHOLOGICAL CHARACTERISTICS OF EARLY PLACENTAL TISSUE IN EARLY PREGNANCY LOSS: A COMPARATIVE STUDY - Norbekov A.Kh.; Ruziyev Sh.I.; Norbekova M.Kh. (Central Asian Journal of Medicine, 2025)
Introduction: Early pregnancy loss remains a significant reproductive challenge, affecting up to 15% of clinically recognized pregnancies. Placental insufficiency and structural abnormalities are increasingly recognized as critical contributors to early gestational failure. This study aimed to investigate histopathological changes in early placental tissue associated with spontaneous abortion and to correlate them with maternal clinical factors. Materials and Methods: A total of 38 placental specimens from first-trimester miscarriage cases (5–12 weeks) and 15 control samples from elective terminations were analyzed. Histological sections were stained with hematoxylin and eosin (H&E) and assessed for villous degeneration, inflammation, necrosis, and hemorrhage. Maternal clinical data, including age, gravidity, prior miscarriages, and lifestyle habits, were also compared. Results: Degenerative villous changes were observed in 84% of the miscarriage group, inflammatory infiltration in 63%, necrosis with fibrinoid deposition in 52%, and intervillous hemorrhage in 47%. These findings were significantly more frequent than in the control group. Maternal age was higher in the miscarriage group (p = 0.014), while other risk factors such as previous miscarriage, smoking, and chronic illness were more prevalent but not statistically significant. Conclusion: Early pregnancy loss is strongly associated with distinct histopathological abnormalities in the placenta, most notably villous degeneration and inflammation. Routine placental examination may provide valuable insights into the etiology of miscarriage and support clinical decision-making for future pregnancies.